Numerical study of contra-rotating Vertical Axis Wind Turbine H-Rotor Darrieus type / Aditya Ilham Setyawan Haryogo, Vivien S. Djanali and Bagus Nugroho - Setyawan Haryogo, Aditya Ilham; S. Djanali, Vivien; Nugroho, Bagus (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
The new Contra-rotating Darrieus turbine configuration has been invented to enhance the Vertical Axis Wind Turbine (VAWT) performance. This configuration increases the relative rotational speed of the generator, resulting in higher output power. It is well known that the increase can reach four times the output power. However, how the Darrieus turbine VAWT contrarotating configuration influences its aerodynamic performance still needs to be discovered. This study investigates the aerodynamic performance of the contra-rotating configuration by comparing it to the single-rotating Darrieus turbine VAWT under the same conditions. The freestream speed is 5 m/s, with TSR varying from one to two intervals of 0.2. This research is being completed using Computational Fluid Dynamics (CFD) 3D cases with an Unsteady Reynold Average Navier-Stokes (URANS) equation as the turbulent model equation. The results of this study show that in terms of output power or Power coefficient (Cp), the contra-rotating has a greater value than the singlerotating configuration. However, in all TSR variations, contra-rotating outperforms single-rotating in terms of aerodynamic performance or moment coefficient (Cm). This is due to the fact that the aspect ratio of stage 1 contra-rotating rotor is lower than the single-rotating rotor, resulting in more significant blade tip losses in contra-rotating. The flow was discovered through the gap between stages 1 and 2 contra-rotating, providing additional momentum. This phenomenon increases Cm at an azimuth angle of 200°-255°.